[PP.24.26] ANTIHYPERTENSIVE EFFECTS OF A CENTRAL ARTERIOVENOUS ANASTOMOSIS ARE MEDIATED THROUGH PROFOUND REDUCTION IN SYSTEMIC VASCULAR RESISTANCE. (September 2017) - SAXENA, M.; Shour, T.; Sobotka, P.; Jain, A.; Collier, D.J.; Hamshere, S.; Mathur, A.; Knight, C.; Lobo, M.D.
Abstract : Objective: The creation of a central iliac arteriovenous (cAV) anastomosis incorporates a segment of vein into the arterial circuit using an anastomotic nitinol coupler device. We present hemodynamic changes following cAV implantation that reveal the potential antihypertensive mechanism of action. Figure. No caption available. Design and method: A 74 year old Caucasian female with chronic uncontrolled hypertension (HTN) (Office BP (OBP) 190/90 mmHg), and stage II chronic kidney disease was treated with the cAV coupler. She was taking liquid Furosemide 20 mg daily due to multiple medication intolerances. The coupler was inserted in a standard catheterization laboratory setting. A fixed calibre 4 mm conduit was created between the right external iliac artery and vein. Hemodynamic changes were evaluated with left and right heart catheterization, OBP and ambulatory BP (ABP). Results: Opening of the coupler led to instantaneous, substantial on-table reduction in mean arterial pressure (MAP) due to a sudden and profound reduction in systemic vascular resistance (SVR) by 38% (see figure and table). There was a corresponding increase in stroke volume (SV; 24%), cardiac output (CO; 39%), and heart rate (HR; 14%) compared to baseline. At 6 months follow up there were further reductions in SVR (50%) and MAP (24%) compared to baseline. There were also immediate (1-day post-coupler), and durable (6-months post-coupler) reductions in OBP (32/19 mmHg) and ABP (16/22mmHg) without medication changes. Conclusions: The dramatic reduction in SVR post coupler insertion has not been previously demonstrated utilising pharmacotherapy or device therapies for HTN. A cAV anastomosis offers a unique mechanical treatment option for HTN and may be of particular benefit in patients with arterial stiffness in whom, sympathomodulation has diminished impact.